Respuesta :

Answer:

  (-1, 0), (-1, -5)

Step-by-step explanation:

The initial translation transformation was ...

  (x, y) ⇒ (x +4, y)

Then the reflection across the line y=x added the transformation ...

  (x, y) ⇒ (y, x)

So, the result of the composition of transformations was ...

  (x, y) ⇒ (y, x+4)

Then the reverse transformation, the one that gets from the image back to the pre-image, will be ...

  (y, x+4) ⇒ (x, y)

  (x, y) ⇒ (y-4, x)

The points A", B", C", D" will be transformed back to pre-image points ...

  A"(-4, 5) ⇒ A(1, -4)

  B"(-1, 5) ⇒ B(1, -1)

  C"(0, 3) ⇒ C(-1, 0) . . . . . . matches an answer choice

  D"(-5, 3) ⇒ D(-1, -5) . . . . . matches an answer choice

ACCESS MORE